2013
DOI: 10.1007/s11606-013-2683-y
|View full text |Cite
|
Sign up to set email alerts
|

Physician Underutilization of Effective Medications for Resistant Hypertension at Office Visits in the United States: NAMCS 2006–2010

Abstract: BACKGROUND:The American Heart Association (AHA) published guidelines for treatment of resistant hypertension in 2008 recommending use of thiazide diuretics (particularly chlorthalidone), aldosterone antagonists, and fixed-dose combination medications, but it is unclear the extent to which these guidelines are being followed. OBJECTIVE: To describe trends in physician use of recommended medications for resistant hypertension and assess variations in medication use based on geography, physician specialty and pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 37 publications
1
20
0
Order By: Relevance
“…These results are consistent with previous cross-sectional studies in the TRH population. 17,18 Using data from the National Ambulatory Medical Care Surveys, Fontil et al 19 observed nonsignificant increases between 2006 and 2010 in the use of β-blockers, CCBs, and aldosterone receptor antagonists, similar to the trends found in our study. In contrast, the authors saw thiazide diuretic use decrease slightly during the study period, whereas we observed no substantial change in the prevalence of thiazide diuretics among TRH regimens.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results are consistent with previous cross-sectional studies in the TRH population. 17,18 Using data from the National Ambulatory Medical Care Surveys, Fontil et al 19 observed nonsignificant increases between 2006 and 2010 in the use of β-blockers, CCBs, and aldosterone receptor antagonists, similar to the trends found in our study. In contrast, the authors saw thiazide diuretic use decrease slightly during the study period, whereas we observed no substantial change in the prevalence of thiazide diuretics among TRH regimens.…”
Section: Discussionsupporting
confidence: 86%
“…Interestingly, we observed an unexpected decrease in the proportion of regimens containing an ACE-I during the study period. Although of a lower magnitude, Fontil et al 19 Our finding that hydrochlorothiazide remains the most commonly used thiazide diuretic is not surprising given its overwhelming use in the general hypertensive population. However, chlorthalidone use remains remarkably low in patients with TRH, despite evidence suggesting its superior BP-lowering ability and possible greater reductions in major adverse cardiovascular outcomes in most, [21][22][23][24] but not all, hypertensive populations.…”
Section: Discussionmentioning
confidence: 92%
“…However, real-world evaluation of practice patterns suggests frequent missed opportunities for appropriate treatment intensification in management of hypertension. 17,[34][35][36][37] The large impact of treatment intensification on population BP control seen in our model argues for large-scale adoption of interventions that have been shown to increase treatment intensification rates. 36,[38][39][40][41] Our results suggest that visit frequency is an important parameter in the management of hypertension.…”
Section: Discussionmentioning
confidence: 89%
“…A recent publication in this journal suggests that patients with resistant hypertension are elderly (mean age 68 years), with a high prevalence of comorbid conditions. 14 The authors noted that, overall, the use of AHArecommended medications for resistant hypertension remains low, despite publication of guidelines targeting this demographic. Given that these patients represent a population at very high risk of cardiovascular events, we are concerned that relaxed blood pressure standards would increase clinical inertia regarding necessary multi-drug therapy for hypertension.…”
mentioning
confidence: 99%